1978
DOI: 10.1021/bi00615a014
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic and chemical properties of an endopeptidase from the larva of the hornet Vespa crabro

Abstract: An endopeptidase from the larvae of the hornet Vespa crabro has been purified to homogeneity. The enzyme has been characterized with respect to molecular weight, amino acid compositon, and amino- and carboxyl-terminal sequences. The catalytic properties of the hornet protease are similar to those of bovine chymotrypsin with respect to inactivation by phenylmethanesulfonyl fluoride and carbobenzoxyphenylalanine chloro ketone and preferential peptide bond cleavage at aromatic amino acid residues. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1981
1981
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Calculation based on the specific activities of purified Pl and P2 and that of the crude extract indicated that PI and P2 together represent about 6-8070 of the proteins in the hepatopancreas extract. The cleavage sites of the shrimp chymotrypsins on oxidized bovine insulin chain B ( fig.2) suggest that their peptide-bond specificities are similar to that of chymotrypsins from crab [2], hornet and Streptomyces griseus [16]. They prefer bonds at the carboxyl side of tyrosyl, phenylalanyl and leucyl residues, and to a lesser extent, those of lysyl, arginyl and glutaminyl residues.…”
Section: Resultsmentioning
confidence: 93%
“…Calculation based on the specific activities of purified Pl and P2 and that of the crude extract indicated that PI and P2 together represent about 6-8070 of the proteins in the hepatopancreas extract. The cleavage sites of the shrimp chymotrypsins on oxidized bovine insulin chain B ( fig.2) suggest that their peptide-bond specificities are similar to that of chymotrypsins from crab [2], hornet and Streptomyces griseus [16]. They prefer bonds at the carboxyl side of tyrosyl, phenylalanyl and leucyl residues, and to a lesser extent, those of lysyl, arginyl and glutaminyl residues.…”
Section: Resultsmentioning
confidence: 93%
“…8). However, the three sequenced invertebrate enzymes (12,13,14) including hornet chymotrypsin, and now this sequenced Drosophila trypsin-like enzyme, all lack the 136-201 bridge. The possibility that either the vertebrate enzymes all picked up the fourth bridge independently or that the invertebrate enzymes all lost the bridge after a single trypsinchymotrypsin divergence is unlikely.…”
Section: Evolution Of the Serine Proteasesmentioning
confidence: 99%
“…iany et al (31) described an endopeptidase belonging to the chymotrypsin family in the larvae of the hornet Vespa crabro, and Yates (32) described trypsin-like enzymes in the female of Aedes aegypty; Garda et al (33) purified a sulphydryl-dependent proteare from Rhodnius prolixus midgut (prolixasa) similar to o, .t yrrotrypsin and not inhibited by TLCK. An alkaline protease of molecular weight 14,000 associated with a granulosis virus of Plodia interpunctella which is inhibited by PMSF has also been described (35) but the action of those enzymes upon fibrinogen has not been studied.…”
Section: Discussionmentioning
confidence: 99%